Elastic aerogel material and preparation method thereof

The dome unit connection formed by a polycrystalline two-dimensional sheet structure composed of nanoparticles is solved, and a high elasticity and complete recovery aerogel material is achieved.

CN119425547AActive Publication Date: 2025-02-14ZHEJIANG UNIV +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411617817.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing aerogel materials have limited their value in practical applications due to the poor elasticity of the macroscopic structure materials connected by zero-dimensional particles.

Method used

By using aerogel material connected by continuous dome units, the dome unit consists of a multi-crystal two-dimensional sheet structure composed of nanoparticles, with micro-scale elastic arch units and multi-scale structures, improving the elasticity of the material.

Benefits of technology

The complete recovery of the aerogel material under 80% deformation is achieved, and the mechanical rebound ability and mechanical stability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425547A_ABST
    Figure CN119425547A_ABST
Patent Text Reader

Abstract

According to the elastic aerogel and the preparation method thereof, a graphene oxide film is mainly used as an aerogel precursor, salt ions are adsorbed through a two-dimensional atomic-scale channel between graphene oxide layers, and preparation of the graphene oxide hybrid aerogel of a micro-dome structure is achieved through plastic dissolving and foaming. And finally, preparing the nano-particle-based aerogel by utilizing high-temperature thermal conversion, wherein the aerogel material is formed by connecting continuous dome units. The dome unit comprises an upper dome and a lower dome which are opposite to each other; the upper dome and the lower dome are each of a two-dimensional lamellar structure composed of nano-particles, the thickness of each lamellar structure is smaller than 100 nm, the lamellar structures have the wrinkle morphology, and the problem that in the prior art, a macrostructure material connected through zero-dimensional particles is poor in elasticity is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to an elastic aerogel material and a preparation method thereof. Background Art

[0002] Aerogels are a class of lightweight materials with low density and high porosity, which have shown wide applications in space exploration, sensing, thermal management and chemical sensing. Since Kistler proposed this concept in 1931, thousands of aerogel types have been developed, including metals, oxides, chalcogenides, carbides, carbon materials, organic materials and multi-components. However, since most of the reported aerogels are composed of intrinsically weak zero-dimensional particle connection structures, they often show brittle mechanical properties and poor resilience, which limits their value in practical applications. Summary of the invention

[0003] The purpose of the present invention is to provide an elastic aerogel material and a preparation method thereof in view of the deficiencies of the prior art. The material is mainly composed of nanoparticles, which overcomes the problem of poor elasticity of macroscopic structural materials connected by zero-dimensional particles in the prior art.

[0004] One of the technical solutions of the present invention is to provide an elastic aerogel. Specifically, the aerogel material is connected by continuous dome units; the dome unit includes a relative upper dome and a lower dome to form a micro-scale elastic arch unit. Both the upper dome and the lower dome are polycrystalline two-dimensional lamellar structures composed of cross-linked nanoparticles. The thickness of the lamellar structure is less than 100 nm, which can prevent the collapse of the three-dimensional framework and maintain the mechanical stability of the ultra-light aerogel. Furthermore, the upper and lower domes have a micro-fold structure. This multi-scale structure effectively improves the elasticity of the aerogel material. During the deformation process, the dome structure can generate a large number of elastic folds along the curvature direction as energy storage units to prevent structural stress concentration, thereby providing the possibility for its recovery after deformation.

[0005] Furthermore, the nanoparticles are one or more of oxide nanoparticles, nitride nanoparticles, carbide nanoparticles, and metal nanoparticles.

[0006] Furthermore, the oxide nanoparticles are one or more of silicon dioxide nanoparticles and metal oxide nanoparticles.

[0007] Furthermore, the two-dimensional layer structure has mesopores, which provides more possibilities for its application in the field of thermal insulation. The two-dimensional layer structure has a polycrystalline structure.

[0008] The second technical solution of the present invention is to provide a method for preparing elastic aerogel, which utilizes the ion adsorption and confinement effect of the interlayer channels of graphene oxide to provide a guarantee for the transformation of zero-dimensional materials into two-dimensional characteristic sheets at high temperature. This method is applicable to almost all zero-dimensional materials, and thus a library of aerogel materials assembled with two-dimensional sheets of micro-dome structures is systematically established. In addition, the wrinkles of graphene oxide derive the wrinkle structure of the dome, which exhibits multi-scale wrinkle behavior during compression, providing higher elasticity for the recovery of the aerogel, thereby ensuring that the aerogels in the prepared material library maintain ultra-high mechanical resilience. Specifically, the method comprises the following steps:

[0009] (1) The graphene oxide film is immersed in a precursor salt solution, and the oxygen-containing groups of each layer of graphene oxide are used to adsorb salt ions and assemble on the surface of atomically thick sheets to obtain a hybrid film. As is common knowledge in the art, any graphene oxide film contains microscopic sheet wrinkle structures to varying degrees.

[0010] (2) The hybrid film is subjected to solution-plastic foaming to prepare a composite aerogel material with a dome structure; the two-dimensional structure of graphene oxide allows the precursor salt to grow in a restricted manner between graphene oxide layers; (3) Placing the hybrid film after solution-plastic foaming in a tubular furnace for aerobic sintering to form oxide particles while removing graphene oxide to obtain an elastic aerogel composed of oxide nanoparticles. As a common technical means in this field, the concentration of the precursor salt solution in the aforementioned step 1 can be adjusted so that the graphene oxide can be completely burned out during the aerobic sintering process.

[0011] During the oxygen sintering process, the precursor salts fuse and grow between the graphene oxide layers. As the temperature rises, these precursors gradually transform into the corresponding oxide nanoparticles and form a polycrystalline structure in situ. These polycrystalline nanoparticles assemble in a sheet-like form, ensuring the mechanical strength and elasticity of the material.

[0012] Furthermore, the method further comprises reducing the elastic aerogel composed of the oxide nanoparticles by using hydrogen or Joule heat to obtain an elastic aerogel composed of reduced nanoparticles, such as metal nanoparticles.

[0013] The third technical solution of the present invention is to provide a method for preparing an elastic aerogel, comprising the following steps: (1) Immersing the graphene oxide film in a precursor salt solution, using the oxygen-containing groups on the graphene oxide surface to adsorb salt ions and assemble on the surface of the atomically thick sheet to obtain a hybrid film; (2) subjecting the hybrid film to solution-plastic foaming; (3) Placing the hybrid film after solution-plastic foaming in a tubular furnace for oxygen-free carbonization treatment to obtain an elastic aerogel composed of carbide nanoparticles. As a common technical means in this field, the concentration of the precursor salt solution in the above step 1 can be adjusted so that the graphene oxide can react with the precursor salt to form a carbide during the oxygen-free carbonization process.

[0014] Under high temperature and oxygen-free conditions, the graphene oxide in the hybrid membrane will be completely carbonized, and at the same time, the precursor salt will decompose and transform into carbide nanoparticles. These nanoparticles will diffuse and fuse with each other at high temperatures to form a polycrystalline structure. The particles of the polycrystalline structure are interconnected to form a stable network structure, thereby maintaining the overall morphology and elasticity of the aerogel.

[0015] A fourth technical solution of the present invention is to provide a method for preparing an elastic aerogel, comprising the following steps: (1) Immersing the graphene oxide film in a precursor salt solution to obtain a hybrid film; (2) subjecting the hybrid film to solution-plastic foaming; (3) Transferring to a solution containing a nitrogen source for further hybridization to provide a nitrogen source for the formation of metal nitrides; (4) placing the graphene in a tube furnace for oxygen-free carbonization treatment, during which the graphene oxide forms a carbon layer, and nitrogen and the precursor salt form nitrides at high temperature; (5) Place the sample in a tubular furnace for oxygen sintering to obtain an elastic aerogel composed of nitride nanoparticles. The carbon layer is burned off under oxygen conditions.

[0016] Furthermore, the solution containing the nitrogen source is urea.

[0017] Furthermore, the precursor salt solution is: a metal salt solution or a silicate solution.

[0018] Furthermore, the solution-plastic foaming is to place the hybrid membrane in a 30% hydrazine hydrate solution for foaming for 30 minutes.

[0019] Furthermore, the aerobic sintering is: sintering at 600-800 degrees Celsius in an aerobic environment; and the anaerobic carbonization is: sintering at 1300-1600 degrees Celsius in an anaerobic environment.

[0020] Beneficial effects of the present invention: (1) The present invention forms a self-supporting high-elastic aerogel through the overall optimization of the structure of zero-dimensional particle-based materials, which can achieve complete recovery under 80% deformation.

[0021] (2) Through the two-dimensional monoatomic interlayer channel adsorption confinement effect of graphene oxide, the universal growth and preparation of two-dimensional materials can be achieved, greatly expanding the material spectrum of two-dimensional sheets.

[0022] (3) The preparation of multi-component aerogel materials was achieved by utilizing the arbitrary miscibility of precursor salts. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a physical picture of the process of preparing the two-dimensional alumina aerogel in Example 1; Figure 2 110 two-dimensional oxide aerogels were prepared by the present invention; Figure 3 38 kinds of two-dimensional carbide aerogels were prepared by the present invention; Figure 4 35 kinds of two-dimensional metal aerogels were prepared by the present invention; Figure 5 The compression-rebound curve of the two-dimensional alumina aerogel prepared in Example 1 after 10,000 compressions; Figure 6 This is an electron microscope image of the two-dimensional metallic copper aerogel prepared in Example 8. DETAILED DESCRIPTION

[0024] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0025] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0026] Many studies have been devoted to improving the mechanical elasticity of monolayer and composite aerogels, usually through the overlapping of one-dimensional (1D) fibers that are entangled or chemically bonded, the stacking of recoverable buckling nanotubes, and the assembly of two-dimensional (2D) nanosheets with biomimetic layered structures to form negative Poisson's ratio structures or microscale elastic arch units. However, the introduction of heterogeneous materials is often not good, and compatibility issues between different materials may cause defects at the interface, thereby affecting the overall performance of the final composite material. Moreover, the structure produced by the existing method is difficult to achieve the universal elasticity of aerogels assembled from different materials. The present invention utilizes the ion adsorption confinement effect of the interlayer channel of single-atom graphene oxide to provide a guarantee for the maintenance of two-dimensional characteristics in the transformation growth of zero-dimensional materials at high temperatures, forming an intrinsic aerogel of nanoparticles, which has wide applicability, high strength, and simple process. The following is a further description of the embodiments of the present invention in multiple embodiments.

[0027] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0028] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0029] The mesopores described in the present invention are pores with a pore diameter of 2-50 nm.

[0030] Those skilled in the art can simply adjust the concentration of the precursor salt solution so that the graphene oxide reacts completely with the precursor salt to form carbides during the subsequent oxygen-free carbonization process, or completely forms carbon dioxide after an oxygen-containing sintering treatment.

[0031] Example 1 The graphene oxide film (purchased from Hangzhou Gaoxin Technology Co., Ltd.) was immersed in a 10 mg / g aluminum chloride salt solution for 6 h, and then dried at room temperature to obtain a hybrid film of graphene oxide and aluminum oxide. It was then placed in a 30% hydrazine hydrate solution for solution-plastic foaming. After foaming for 30 min, it was taken out and the residual solvent on its surface was washed away with ethanol. After being placed at room temperature for drying, a hybrid aerogel of graphene oxide and aluminum chloride hydrate was obtained. It was placed in a muffle furnace at 600 degrees Celsius for 4 h to obtain a translucent two-dimensional aluminum oxide aerogel with a density of 0.86 mg / cm 3 , after 10,000 cycles of 80% compression strain, the plastic deformation is only 4.5%.

[0032] Example 2 Same as Example 1, except that the salt solution was replaced with chromium chloride, a green two-dimensional chromium oxide aerogel was prepared with a density of 1.21 mg / cm 3 , after 10,000 cycles of 80% compression strain, the plastic deformation is only 3.1%.

[0033] Example 3 Same as Example 1, except that the salt solution was replaced with copper chloride, a purple two-dimensional copper oxide aerogel was prepared with a density of 1.11 mg / cm 3 , after 10,000 cycles at a compressive strain of 60%, the plastic deformation is only 1.1%.

[0034] Example 4 Same as Example 1, except that the salt solution was changed to hafnium chloride and the concentration was changed to 100 mg / g, a white two-dimensional hafnium oxide aerogel was prepared with a density of 20.11 mg / cm 3 , after 10,000 cycles at 80% compressive strain, the plastic deformation is only 2.5%.

[0035] Example 5 Similar to Example 4, the prepared hybrid aerogel of graphene oxide and hydrated hafnium chloride was placed in a tubular furnace for heat treatment under argon atmosphere protection at 1600 degrees Celsius for 2 hours. After cooling, carbonized hafnium aerogel was obtained, and its density was 8.76 mg / cm 3 , after 10,000 cycles of 90% compression strain, the plastic deformation is only 3.5%.

[0036] Example 6 The same as Example 1, wherein the salt solution was changed to tetraethyl orthosilicate, and the concentration was changed to 100 mg / g. After foaming with hydrazine hydrate, a hybrid aerogel of graphene oxide and silicon dioxide was realized, which was placed in a tubular furnace for heat treatment, argon atmosphere protection, 1600 degrees Celsius for 4 hours, and after cooling, a silicon dioxide aerogel was obtained, and its density was 10.76 mg / cm 3 , after 10,000 cycles of 90% compressive strain, the plastic deformation is only 2.2%.

[0037] Example 7 The same as Example 1, wherein the concentration of aluminum chloride is 100 mg / g, the hybrid aerogel of graphene oxide and aluminum chlorohydrate is obtained, and is placed in a 100 mg / g urea solution for immersion to provide a nitrogen source for the formation of aluminum nitride. The sample is then dried and placed in a tubular furnace for heat treatment under nitrogen atmosphere protection at 1300 degrees Celsius for 4 hours, and then placed in a muffle furnace at 800 degrees Celsius for 4 hours to remove graphene oxide. After cooling, aluminum nitride aerogel is obtained, and its density is 8.52 mg / cm 3 , after 10,000 cycles at 60% compressive strain, the plastic deformation is only 6.2%.

[0038] Example 8 As in Example 3, the obtained copper oxide aerogel was placed in a tubular furnace and thermally reduced in a 20% hydrogen atmosphere at a reduction temperature of 500 degrees for 1 hour. After cooling, metallic copper aerogel was obtained with a density of 2.34 mg / cm 3 , after 10,000 cycles at a compressive strain of 60%, the plastic deformation is only 8.8%.

[0039] Example 9 As in Example 1, the obtained alumina aerogel was placed between two layers of artificial graphite films, and a pulse current was applied to the graphite film with a pulse time of 100 ms for 10 cycles to ensure that the temperature of the graphite film surface reached above 2000 degrees. After cooling, a metal aluminum aerogel was obtained with a density of 0.75 mg / cm 3 , after 10,000 cycles at a compressive strain of 60%, the plastic deformation is only 12.9%.

[0040] Example 10 The same as in Example 1, except that the salt solution was replaced by a mixed solution of aluminum chloride and cerium chloride, a two-dimensional aluminum oxide cerium binary oxide aerogel was prepared, and its density was 1.56 mg / cm 3 , after 10,000 cycles at 80% compressive strain, the plastic deformation is only 3.7%.

[0041] Embodiment 11 As in Example 5, the salt solution was changed to a mixed solution of hafnium chloride and tantalum chloride to prepare a two-dimensional hafnium tantalum oxide binary carbide aerogel with a density of 1.22 mg / cm 3 , after 10,000 cycles of 90% compressive strain, the plastic deformation is only 3.1%.

[0042] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.

Claims

1. An elastic aerogel material, characterized in that: The material is formed by connecting continuous dome units; the dome units include an upper dome and a lower dome opposite to each other; Both the upper dome and the lower dome are two-dimensional lamellar structures composed of nanoparticles. The thickness of the lamellar structure is less than 100 nm and has a wrinkled morphology.

2. The elastic aerogel material according to claim 1, characterized in that: The nanoparticles are one or more of oxide nanoparticles, nitride nanoparticles, carbide nanoparticles, and metal nanoparticles.

3. The elastic aerogel material according to claim 2, characterized in that: The oxide nanoparticles are one or more of silicon dioxide nanoparticles and metal oxide nanoparticles.

4. The elastic aerogel material according to claim 1, characterized in that: The two-dimensional layer structure has a polycrystalline structure.

5. The elastic aerogel material according to claim 1, characterized in that: The two-dimensional sheet structure has mesopores.

6. A method for preparing the elastic aerogel material as claimed in claim 1, characterized in that: The following steps are involved: (1) Immersing the graphene oxide film in a precursor salt solution to obtain a hybrid film; (2) subjecting the hybrid film to solution-plastic foaming; (3) The hybrid film after solution-plastic foaming is placed in a tubular furnace for aerobic sintering to obtain an elastic aerogel composed of oxide nanoparticles.

7. The preparation method according to claim 6, characterized in that: The method also includes reducing the elastic aerogel composed of the oxide nanoparticles to obtain the elastic aerogel composed of the reduced nanoparticles.

8. A method for preparing the elastic aerogel material as claimed in claim 1, characterized in that: The following steps are involved: (1) Immersing the graphene oxide film in a precursor salt solution to obtain a hybrid film; (2) subjecting the hybrid film to solution-plastic foaming; (3) Placing the hybrid film after solution-plastic foaming in a tubular furnace for oxygen-free carbonization treatment to obtain an elastic aerogel composed of carbide nanoparticles.

9. A method for preparing the elastic aerogel material as claimed in claim 1, characterized in that: The following steps are involved: (1) Immersing the graphene oxide film in a precursor salt solution to obtain a hybrid film; (2) subjecting the hybrid film to solution-plastic foaming; (3) Transfer to a solution containing a nitrogen source for further hybridization; (4) Place in a tube furnace for oxygen-free carbonization treatment; (5) The resultant product is placed in a tubular furnace for oxygen sintering to obtain an elastic aerogel composed of nitride nanoparticles.

10. The preparation method according to claim 9, characterized in that: The solution containing the nitrogen source is urea.

11. The preparation method according to any one of claims 6 to 10, characterized in that: The precursor salt solution is: a metal salt solution or a silicate solution.

12. The preparation method according to any one of claims 6 to 10, characterized in that: Solution foaming is to place the hybrid membrane in a 30% hydrazine hydrate solution and foam it for 30 minutes.

13. The preparation method according to any one of claims 6 to 10, characterized in that: The aerobic sintering is: sintering at 600-800 degrees Celsius in an oxygen environment; the oxygen-free carbonization is: sintering at 1300-1600 degrees Celsius in an oxygen-free environment.

Citation Information

Patent Citations

  • Graphene and oxide ceramic composite material and preparation method

    CN102603271A

  • Graphene composite material, and preparation methods and application thereof

    CN106531975A

  • MXene / metal composite aerogel, preparation method and applications thereof, and thermal interface material containing MXene / metal composite aerogel

    CN110628155A

  • High-temperature-resistant elastic graphene aerogel and preparation method thereof

    CN111974320A

  • MXene composite foam constructed based on polyurethane foaming principle and preparation method of MXene composite foam

    CN112300363A